Bridging Strategy and Local Reality: First-Line Managers' Experiences in Leading Large-Scale Implementation. - Viktorsson, Lisa; Skagerström, Janna; Gustafsson, Christine; Dannapfel, Petra (Health Services Insights, 2026)
Background: Implementation of eHealth technologies has the potential to improve healthcare delivery, but is complex. Successful adoption depends on organizational readiness, effective change management and active involvement of healthcare professionals. Leadership plays a critical role in fostering a supportive climate for digital transformation. However, many managers lack the tools, knowledge and clarity needed to lead implementations effectively. This study explores how middle managers in primary care in Sweden prepare for and lead a large-scale, top-down implementation of a digital service system (1177 Direct) for symptom assessment, triage, referral and chat. Objectives: By examining middle managers' experiences, the study aims to identify best practices, barriers and enabling factors that support successful digital transformation. Methods: Semi-structured interviews were conducted with 26 middle managers within primary healthcare. Interviews were conducted 2 weeks before each unit launched the digital service system. The data were analysed using conventional content analysis. Results: The analysis yielded four categories describing the managers' experiences of preparing for implementation of the digital service at their workplace: (1) how the managers navigated their role when driving top-down organizational change, having the responsibility to lead the change no matter their thoughts about it; (2) the importance of preparing tailored strategies for the implementation; (3) important preconditions for leadership in change; (4) the ability to adjust the innovation and implementation process to the local setting. Conclusion: Middle managers have a pivotal role in preparing for and leading implementation. Managers' efforts focused on supporting staff, navigating uncertainty, and applying local strategies to foster readiness and engagement. When leading change, there is a need for clear communication, contextual adaptation and bidirectional feedback to ensure sustainable implementation. Strengthening these preconditions can enhance middle managers' capacity to lead complex digital transformations effectively and promote long-term success.